1993
DOI: 10.2466/pms.1993.77.3.776
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Construals of Tic-Producing Situations following Cognitive and Behavioral Therapy

Abstract: 12 clients suffering from chronic tics participated in one of two treatment programs, either a behavioral group using competing response therapy or a group using Beck-style cognitive restructuring. A repertory grid based upon the personal construct psychology of George Kelly was administered to all clients before and after treatment. The grid comprised a set of elements made up of situations with high, medium, and low risk of eliciting tics, and constructs were derived from comparisons between them. Clients' r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…O’Connor and colleagues (O’Connor, Brisebois, Brault, Robillard, & Loiselle, 2003; O’Connor, Gareau, & Blowers, 1993; 1994) identified situations in which tics or habits were likely to appear and situations in which tics were weak or even absent by using Kelly’s repertory grid technique. Socializing was the most frequently named high-risk activity, while studying was most frequently named as low-risk activity.…”
Section: Association Between Psychosocial Stress and Ticsmentioning
confidence: 99%
“…O’Connor and colleagues (O’Connor, Brisebois, Brault, Robillard, & Loiselle, 2003; O’Connor, Gareau, & Blowers, 1993; 1994) identified situations in which tics or habits were likely to appear and situations in which tics were weak or even absent by using Kelly’s repertory grid technique. Socializing was the most frequently named high-risk activity, while studying was most frequently named as low-risk activity.…”
Section: Association Between Psychosocial Stress and Ticsmentioning
confidence: 99%
“…Thus, TD and BFRB patients report an urge or impulse to perform the motor act (i.e., the tic or the repetitive behavior) and both experience relief after it has occurred [ 10 , 11 , 12 , 13 ]. In both conditions, chronic symptoms wax and wane, follow the same loop of negative reinforcement, and can be accentuated by stress, fatigue, or boredom [ 1 , 14 , 15 ]. To our knowledge, no study has reported the comorbidity rates between tic disorders and BFRB as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Of these initial 29 articles, 5 non-English-language studies (Aguilar & Boehrt, 1983;Araki & Nakai, 1990;Araki & Okuma, 1985;Bados Lopez & Olle, 1984;Cloutier, 1985) were excluded from our review because of difficulties in accessing and translating the articles. In addition, we excluded three case studies (O'Brien & Brennan, 1979;Young & Montano, 1988;Zikis, 1983) and one report that did not provide sufficient information regarding the independent variable or experimental design (O'Connor, Gareau, & Blowers, 1993). In total, 20 studies remained in the database for methodological analysis according to the areas described below.…”
Section: Methods Literature Searchmentioning
confidence: 99%